(untitled) - Clouse, Barbara Fine. (New York, 2010)
Pt.1. Strategies for Reading and Writing ; Pt.2. Patterns of Development ; Pt.3. Using the Patterns of Development ; Pt.4. A Brief Guide to Sentence Errors.
Keywords: English language,Ngôn ngữ Anh; Rhetoric,Tu từ học